2022
DOI: 10.1186/s12889-022-12879-6
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate housing and pulmonary tuberculosis: a systematic review

Abstract: Background Tuberculosis (TB) is a global health issue that has long threatened and continues to threaten human health. While previous studies are important in the search for a cure for TB, to eradicate the disease it is also crucial to analyze environmental influences. Therefore, this study determined the potential effect of inadequate housing on TB and the magnitude of the effect. Methods This is a systematic review of the effects of inadequate ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Prisoners incarcerated in overcrowded cells with poor ventilation were 0.39 times more likely to have TB than those who were incarcerated in small cells with good ventilation. It is supported by other studies conducted elsewhere, which reported that both inadequate ventilation and crowded living conditions increase the risk of contracting TB 69–71 . Because there are not enough TB prevention and control initiatives in prisons and there is not enough access to health and referral services, the high TB incidence among chronic coughers may be explained by these factors.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Prisoners incarcerated in overcrowded cells with poor ventilation were 0.39 times more likely to have TB than those who were incarcerated in small cells with good ventilation. It is supported by other studies conducted elsewhere, which reported that both inadequate ventilation and crowded living conditions increase the risk of contracting TB 69–71 . Because there are not enough TB prevention and control initiatives in prisons and there is not enough access to health and referral services, the high TB incidence among chronic coughers may be explained by these factors.…”
Section: Discussionmentioning
confidence: 54%
“…It is supported by other studies conducted elsewhere, which reported that both inadequate ventilation and crowded living conditions increase the risk of contracting TB. [69][70][71] Because there are not enough TB prevention and control initiatives in prisons and there is not enough access to health and referral services, the high TB incidence among chronic coughers may be explained by these factors. This may also be related to insufficient screening of prisoners upon entry into the facilities, poor ventilation, overcrowding, a lack of early case identification, and a lack of periodic TB screening for prisoners (concerns related to accessibility and the application of recommended screening strategies).…”
Section: Discussionmentioning
confidence: 99%
“…The living environment affects exposure risk to TB. For instance, poor ventilation, overcrowding, and homelessness or housing instability increase the likelihood of exposure to M. tuberculosis and therefore increase the risk of TB infection [54]. Poverty and hunger increase susceptibility to both infection and progression to disease, along with the severity of TB [46].…”
Section: Socioeconomic Determinantsmentioning
confidence: 99%
“…Several risk factors of pulmonary tuberculosis are malnutrition, indoor air quality, the volume of Air Changes per Hour (ACH), ventilation area, lighting intensity, relative humidity levels, and residential overcrowding (7)(8)(9)(10). Houses or buildings are vulnerable places, transmitting airborne diseases, including tuberculosis.…”
Section: Introductionmentioning
confidence: 99%